Histopathological comparisons of Staphylococcus aureus and Pseudomonas aeruginosa experimental infected porcine burn wounds. Issue 3 (18th May 2017) - Chaney, Sarah B.; Ganesh, Kasturi; Mathew‐Steiner, Shomita; Stromberg, Paul; Roy, Sashwati; Sen, Chandan K.; Wozniak, Daniel J.
ABSTRACT: Chronic skin wounds are a significant human health concern and are often complicated by infection with Pseudomonas aeruginosa and Staphylococcus aureus, particularly methicillin resistant S. aureus (MRSA). Translating the knowledge gained from extensive study of virulence mechanisms and pathogenesis of these bacterial species to new treatment modalities has been lacking in part due to a paucity of animal models able to recapitulate human disease. Our groups recently described a novel porcine chronic burn wound model for the study of bacterial infection; however, the histopathology of infection has yet to be described. The objective of this study is to define the histopathology of this model using important human chronic wound bacterial isolates. Porcine full‐thickness burn wounds topically inoculated with P. aeruginosa strain PAO1, MRSA S. aureus strain USA300 or both bacteria were used to define and quantify histopathologic lesions. The development of a systemic, well‐defined rubric for analysis allowed for evaluation of differences between infection groups. These differences, which included epithelial migration and proliferation, stromal necrosis, fluid accumulation and intensity and character of the innate and adaptive inflammatory cell responses, were identified temporally between infection groups. Mono‐species infected wounds developed a hyper‐proliferative wound edge. Coinfected wounds at day 35 had the largest wound sizes, increased amounts of neutrophilic inflammation, immaturity of the wound bed, and retention of necrotic tissue. Infection, regardless of species, inhibited wound contracture at all time points evaluated. Most importantly, this model recapitulated key features of chronic human wounds. Thus, this model will allow researchers to study novel treatment modalities in a biologically relevant animal model while monitoring both host and bacterial responses.